Temporomandibular disorder and serum levels of progesterone and estrogen: Systematic review (Research, Society and Development, 2021)
Temporomandibular Disorder (TMD) is a pathology of the stomatognathic system characterized by a set of clinical disorders that includes a temporomandibular joint, a masticatory musculature and associated structures. It is the most common orofacial pain condition of non-dental origin and which is increasing among adults in the age group between 18 and 45 years with a not well defined etiology, mainly not with regard to its higher prevalence in women than men. The present study aimed to evaluate the literature if there is a relationship between the levels of progesterone and estrogen with the clinical manifestations of TMD. The systematic search was carried out in the following electronic databases: PubMed, Web of Science, SciELO, and LILACS, Scopus, Embase and Google Scholar in addition to a complementary manual search of cross-references of original articles. There was no time restriction. The descriptors used were "TMD" or "TMJ" and "progesterone" and "estrogen". Initially, 132 articles were found, were 15 presented the eligibility criteria to be read in full. In the end, 4 studies were included in the review. The conclusion was that most studies relate the variations of progesterone and estrogen to the symptoms of the disease; however, there are differences between them. Thus, it is recommended to carry out studies that analyze this relationship, leading to hormonal fluctuations ranging from reproductive age to post-menopause.